Islamic Review of Spiritual Intelligence - Haryanto, Sri (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
This study explores the concept of spiritual intelligence from an Islamic perspective. Through literature research, the author investigates various sources that discuss spiritual intelligence from an Islamic point of view. The method used in this study is an analysis of literature relevant to spiritual intelligence in Islam. The primary sources used include the holy book of the Quran, hadith, works of scholars, and previous research that has been done in this field. The results of this study reveal that spiritual intelligence from an Islamic perspective involves the development of an individual's relationship with God, increased self-awareness, and increased morality. Spiritual intelligence enables individuals to balance material and spiritual dimensions, improve the quality of life, and achieve blessings in all aspects of life. The implications of this research can be used in the development of the education field and help individuals achieve goals and happiness in life.